Comparative diving behaviour and segregation of the marine habitat by breeding Royal Penguins, Eudyptes schlegeli, and eastern Rockhopper Penguins, Eudyptes chrysocome filholi, at Macquarie Island - Hull, Cindy L (Canadian Journal of Zoology, 2000)
Comparative use of the water column by Royal Penguins, Eudyptes schlegeli, and eastern Rockhopper Penguins, Eudyptes chrysocome filholi, was examined by comparing their diving behaviour at Macquarie Island during the 1993-1994, 1994-1995, and 1995-1996 breeding seasons. Fifty-eight deployments of time-depth recorders measured depth and duration of dives, time spent submerged, bottom time, occurrence of wiggles, and descent and ascent rates. Both species dived predominantly during daylight hours (4:00-21:00 local time), with shallower dives around midday. Royal and Rockhopper penguins spent 38.9 ± 8.9 and 36.6 ± 9.3% of a 24-h period under water, respectively, but Rockhopper Penguins performed more dives (14.8 ± 9.4/h) of shorter duration (1.2 ± 0.7 min) than did Royal Penguins (11.1 ± 6.9 dives/h; 1.7 ± 0.6 min). Although both could dive to over 100 m, they rarely did so, with Royal and Rockhopper penguins making 79 ± 0.13 and 91 ± 0.08% of their dives to depths of less than 60 m, respectively. Although the difference was not significant, Royal Penguins dived in deeper water (32.9 ± 25.6 m) than did Rockhopper Penguins (27.3 ± 20.3 m). However, Royal Penguins performed wiggles (assumed foraging activity) in water significantly deeper (47.7 ± 24.3 m) than did Rockhopper Penguins (41.3 ± 19.0 m). Royal Penguins also performed more dives with wiggles than Rockhopper Penguins, suggesting differences in foraging technique. The amount of time both spent at the bottom of dives increased across the breeding season from incubation to chick rearing. As dive durations and ascent and descent rates did not change during this time, dive angles must have changed. There were no interannual differences in the diving behaviour of Royal Penguins, but Rockhopper Penguins exhibited differences in dive depths and durations and in the amount of bottom time. Royal Penguins, unlike Rockhopper Penguins, performed fewer dives on the first day of foraging trips, indicating more travelling and less foraging, which reflects differences in ...